Education Enhancement Results Learning Troubleshooting Using Realistic Mathematic Education Approach in Elementary School - Mimik Fernandes (Postgraduate School, Universitas Negeri Padang, 2019)
Abstract , Based on experience and reflection multiplication of fractions learning at fifth class SDN 33 VII Koto Padang Pariaman district. Student learning outcomes are still low and learning is done by teachers are not using realistic problem to the beginning of learning . So the author through this research is trying to improve students' outcomes in subjects multiplication of fractions. The purpose of this study is to describe the planning, implementation and learning outcomes. This research is action research (class action research), this study used a qualitative and quantitative approach. Learning is used by using the realistic mathematics education approach. After doing research, there is an increase in student learning outcomes in the multiplication of fractions lesson using the realistic mathematics education approach . It can be seen, both from the abilities of teachers in designing learning from 83 % up to 94 %, implementation of learning increased 94% from 77%, and learning outcomes increased to 86.87 from 74.04 .